Serologic evidence of the exposure of small mammals to spotted-fever Rickettsia and Rickettsia bellii in Minas Gerais, Brazil - Coelho, Marcella Gonçalves; Ramos, Vanessa do Nascimento; Limongi, Jean Ezequiel; de Lemos, Elba Regina Sampaio; Guterres, Alexandro; da Costa Neto, Sócrates Fraga; Rozental, Tatiana; Bonvicino, Cibele Rodrigues; D'Andrea, Paulo Sérgio; Moraes-Filho, Jonas; Labruna, Marcelo Bahia; Szabó, Matias Pablo Juan (The Journal of Infection in Developing Countries, 2016)
Introduction: Sources of pathogenic Rickettsia in wildlife are largely unknown in Brazil. In this work, potential tick vectors and seroreactivity of small mammals against four spotted-fever group Rickettsia (R. rickettsii, R. parkeri, R. amblyommii and R. rhipicephali) and Rickettsia bellii from peri-urban areas of Uberlândia, a major town in Brazil, are described for the first time. Methodology: Small mammals were captured and blood samples collected. Ticks were collected from the surface of the host and the environment and posteriorly identified. Reactivity of small mammal sera to Rickettsia was tested by indirect immunofluorescence assay (IFA) using crude antigens from five Brazilian Rickettsia isolates. Results: Information was obtained from 416 small mammals (48 Marsupialia and 368 Rodentia). Forty-eight animals were parasitized and two tick species, Ixodes loricatus and Amblyomma dubitatum, were found on several host species, with a few tick-host relationships described for the first time. From the 416 tested sera, 70 reacted to at least one Rickettsia antigen (prevalence of 16.8%) and from these, 19 (27.1%) reacted to two or more antigens. Seroprevalence was higher for marsupials (39.6%) than for rodents (13.8%). Marsupial and Rhipidomys spp. sera reacted mainly (highest seroprevalence and titers) to R. bellii, and that of Necromys lasiurus mainly to R. rickettsii. Conclusions: Although the serologic assays poorly discriminate between closely related spotted-fever group Rickettsia, the observed small mammal seroreactivity suggests the circulation of Rickettsia in the peri-urban area of Uberlândia, albeit at low levels.